Una economía que sirva para vivir. Recorrido por las construcciones económicas del feminismo (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Traditionally women dedicated duties have necessary to be included in the Economy from a triple perspective: equality for in-home duties and tasks, at the same levelas the ones in the public arena; hierarchy reversal, giving priorities to in-home spacesand the rise of a new concept “life sustainability”. First two are known as part of the Feminist Conciliation Economy while the third one is called Feminist Breaking offEconomy. Let the female vision to be introduced into the Economy it is not only agender perspective, but also implies to put the life sustainability in the centre of thedebate- not the market- and work towards sustainability reports in social responsibility,even for men!. It is a claim to human life sustainability and Economy as theprocess of satisfying necessities and creation of resources for well-living. This is why feminist economy rewrites the logical framework of “economics”, doubting about itsprincipals: dichotomies as working/not working, public/private, market/gratuity.
Keywords: Feminist economy; Care economy; Women; Home economy; Well living.